王阳明诗韵研究: A Study on the Rhyme of Wang Yang-ming’s Poetry - Yan CUI, 崔彦 (Journal of Sinological Studies 漢學研究學刊, 2023)
Based on the Wang Yang-ming QuanJi（《王阳明全集》）published by Shanghai Classics Publishing House（上海古籍出版社）in 2011, this paper studies the rhyme features of Wang Yang-ming’s guti shi（古体诗，old style poem）and jinti shi（近体诗, new style poem）respectively. There are 188 verses and 227 stanzas in Wang Yang-ming’s own guti shi, which can be divided into 16 Rhyme Groups. Compared with the GuangYun （《广韵》）, this Rhyme Groups has been simplified. The prominent features are as follows: Zhi Rhyme Group rhymed with Yu Rhyme Group in Yinsheng Rhyme（阴声韵），finals have been merged in Yangsheng Rhyme（阳声韵）and in Rusheng Rhyme（入声韵）. There are 313 verses in Wang Yangming’s own jinti shi which can be divided into 27 Rhyme Groups. This paper holds that jinti shi reflects actual speech by means of jieyun（借韵）and chuyun（出韵）. The degree to which Wang Yangming’s jinti shi that follows the official rhyme is 89.5%, and the one that reflects the actual sound is 10.5%.